Research on 3D Reconstruction Technology of Tool Wear Area - Xiao, Maohua; Sun, Zhenmin; Shen, Xiaojie; Shi, Liping; Zhang, Jing (Manufacturing Technology Journal, 2019)
The operators' poor adaptability on photos and difficulties of removing background point and noise point and other problems make the conventional focusing synthesis techniques difficult to get better application and promotion in the field of three-dimensional reconstruction. In this paper, a modified Laplacian operator was used as an evaluation basis to select focus points and the theory of three-dimensional reconstruction was discussed from the perspectives of image multilayer composite algorithm and height interpolation. To solve the problem of removing noise point and background point, a double threshold selection technique was proposed, which greatly improved the adaptability of focusing evaluation operator. Finally, a test on three-dimensional reconstruction of the tool wear's surface topography was conducted.
Keywords: Tool wear; Three-dimensional reconstruction; Focusing synthesis techniques; Double threshold